The God Equation in the Definition of Life - Subba Rao, Y. V. (European Journal of Applied Sciences, 2022)
While “Origin of Life” is critical to ‘Evolution’ itself, an unequivocal definition of ‘Life’ is even more critical to these two. It is the most fundamental scientific question that needs ‘Life’ to be precisely defined as an equation which remains unanswered in the 21st century. In the present study, an attempt is made to turn to find a solution from religion after satisfying that the so-called religion rests on solid foundation of science of an electromagnetic wave of light involving oscillating magnetic and electric fields, wavelengths/frequencies, and energy interacting with matter as valuable as Einstein’s (God Equation) or the invention of the transistor.